PROMOTING PROBLEM-BASED LEARNING THROUGH COLLABORATIVE WRITING - Patrick Ng Chin Leong (The English Teacher, 2008)
PBL (promoting problem-based learning) is a curriculum model that emphasizes the effective use of problems through an approach of active and multidisciplinary learning. The approach is primarily student-centred (Wilkerson, 1996) and the student assumes the major responsibility for his or her learning. Rather than the tutor dispensing the syllabic content, the students decide and discover for themselves what they will learn. In PBL, students experience a problem as the trigger and motivator for learning. PBL is a powerful tool that can be used to encourage university students to negotiate task-based projects in English. In this article, I will investigate the response of a class of engineering students in Singapore in learning Technical Writing through the PBL approach.